Genome-Wide Association Study of COVID-19 Outcomes Reveals Novel Host Genetic Risk Loci in the Serbian Population - Zecevic, Marko; Kotur, Nikola; Ristivojevic, Bojan; Gasic, Vladimir; Skodric-Trifunovic, Vesna; Stjepanovic, Mihailo; Stevanovic, Goran; Lavadinovic, Lidija; Zukic, Branka; Pavlovic, Sonja; Stankovic, Biljana (Frontiers in Genetics, 2022)
Host genetics, an important contributor to the COVID-19 clinical susceptibility and severity, currently is the focus of multiple genome-wide association studies (GWAS) in populations affected by the pandemic. This is the first study from Serbia that performed GWAS of COVID-19 outcomes to identify genetic risk markers of disease severity. A group of 128 hospitalized COVID-19 patients from the Serbian population was enrolled in the study. We conducted GWAS comparing (1) patients with pneumonia (n = 80) versus patients without pneumonia (n = 48), and (2) severe (n = 34) against mild disease (n = 48) patients, using a genotyping array followed by imputation of missing genotypes. We have detected a significant signal associated with COVID-19 related pneumonia at locus 13q21.33, peaking upstream of the gene KLHL1 (p = 1.91x10-8). Also, our study replicated previously reported COVID-19 risk locus at 3p21.31, identifying lead variants in SACM1L and LZTFL1 genes suggestively associated with pneumonia (p = 7.54x10-6) and severe COVID-19 (p = 6.88x10-7), respectively. Suggestive association with COVID-19 pneumonia has also been observed at chromosomes 5p15.33 (IRX, NDUFS6, MRPL36, p = 2.81x10-6), 5q11.2 (ESM1, p = 6.59x10-6), and 9p23 (TYRP1, LURAP1L, p = 8.69x10-6). The genes located in or near the risk loci are expressed in neural or lung tissues, and have been previously associated with respiratory diseases such as asthma and COVID-19 or reported as differentially expressed in COVID-19 gene expression profiling studies. Our results revealed novel risk loci for pneumonia and severe COVID-19 disease which could contribute to a better understanding of the COVID-19 host genetics in different populations.